Dynamic and thermodynamic impact of L94A, W100A, and W100L mutations on the D2 dopamine receptor bound to risperidone. Issue 53 (30th November 2022) - Azam, Faizul; Bello, Martiniano
Abstract : DRD2 is an important receptor in the mediation of antipsychotic drugs but also in Parkinson medication, hyperprolactinemia, nausea and vomiting. Abstract : DRD2 is an important receptor in the mediation of antipsychotic drugs but also in Parkinson medication, hyperprolactinemia, nausea and vomiting. Recently, crystallographic studies of the DRD2–risperidone complex have provided important information about risperidone recognition in wild-type and different stabilizing DRD2–risperidone residues. Using the crystallographic structure of the DRD2–risperidone complex as a starting point, we undertook molecular dynamics (MD) simulations to investigate the structural and thermodynamic basis of molecular recognition by risperidone at the ligand-binding sites of wild-type and mutant DRD2. A solvated phospholipid bilayer was used to construct DRD2–risperidone complexes, which were then subjected to several microsecond (μs) MD simulations in order to obtain realistic receptor–ligand conformations under the equilibrated simulation time. Risperidone had a higher affinity for wild-type and L94A mutant DRD2 than the W100L and W100A mutants, according to binding free energy calculations using the Molecular Mechanics Generalized-Born Surface Area (MMGBSA) method, explaining the experimental differences in ligand residence times. Principal component (PC) analysis revealed important conformational mobility upon molecular recognition of risperidone for the L94A mutant compared to the wild type, indicating an unfavorable entropic component that may contribute to improving risperidone affinity in the L94A DRD2 mutant.